Pandangan Tokoh Agama Islam dalam Menyikapi Pandemi Covid-19 - Nurjanah, Siti; Rahman, Mohammad Taufiq; Halim, Ilim Abdul (Hanifiya: Jurnal Studi Agama-Agama, 2021)
The Covid-19 problem that continues to haunt public life impacts the implementation of religion in society. For this reason, faith has moved itself to overcome the prevention that has been carried out. Religion plays a significant role in regulating human life, so religious leaders are always expected to provide guidance and religious doctrine in responding to covid 19. The purpose of this study was to find out about the views of Islamic religious leaders and from religious doctrine itself in responding to the Covid pandemic. -19. The method used is the descriptive qualitative research method. Primary data sources are sources taken directly from religious organization figures such as Nahdlatul Ulama, Persatuan Islam, and Muhammadiyah. The secondary data sources are literature such as books, journals, and other scientific works to collect data systematically. Data analysis was carried out in several ways, namely data reduction, data presentation and verification. Religious institutions also have a role in the community in responding to the Covid-19 outbreak, namely moving in helping the community, providing solutions and contributing according to government regulations to the community. In matters of worship, the community must know whether the rules of congregational worship are allowed or not and whether other sacred places are allowed to be visited. It all goes into the role of religious institutions in guiding the community.